A Simple Score to Identify Super-Responders to Sacubitril/Valsartan in Ambulatory Patients With Heart Failure - Moliner-Abós, Carles; Mojón Álvarez, Diana; Rivas-Lasarte, Mercedes; Belarte, Laia Carla; Pamies Besora, Julia; Solé-González, Eduard; Fluvià-Brugues, Paula; Zegrí-Reiriz, Isabel; López López, Laura; Brossa, Vicens; Pirla, Maria José; Mesado, Nuria; et al. (Frontiers in Physiology, 2021)
Introduction: Sacubitril/Valsartan (SV) promotes cardiac remodeling and improves prognosis in patients with heart failure (HF). However, the response to the drug may vary between patients and its implementation in daily clinical practice has been slower than expected. Our objective was to develop a score predicting the super-response to SV in HF outpatients. Methods: This is a retrospective analysis of 185 consecutive patients prescribed SV from two tertiary hospitals between September 2016 and February 2018. Super-responder was defined as a patient taking the drug and (i) without HF admissions, death or heart transplant, and (ii) with a ≥50% reduction in NT-proBNP levels and/or an increase of ≥10 points in LVEF in a 12-month follow-up period after starting SV. Clinical, echocardiographic, ECG, and biochemical variables were used in a logistic regression analysis to construct a score for super-response to SV which was internally validated using bootstrap method. Results: Out of 185 patients, 65 (35%) fulfilled the super-responder criteria. Predictors for super-response to SV were absence of both previous aldosterone antagonist and diuretic treatment, NYHA I-II class, female gender, previous 1-year HF admission, and sinus rhythm. An integrating score distinguished a low- (<25%), intermediate- (~46%) and high-probability (>80%) for 1-year super-response to SV. The AUC for the model was 0.72 (95%CI: 0.64-0.80), remaining consistent after internal validation. Conclusion: One third of our patients presented a super-response to SV. We propose an easy-to calculate score to predict super-response to SV after 1-year initiation based on variables that are currently assessed in clinical practice.